Parliaments and political change in Asia - Runland, Jurgen 1953-; Institute of Southeast Asian Studies (Singapore Institute of Southeast Asian Studies, 2005)
"Examines the specific roles of parliaments in political decision-making, regime change, democratization, and consolidation of democracy in a comparative perspective."--GVRL description.
Keywords: Legislative bodies -- Asia; Representative government and representation -- Asia; Electronic books; Asia -- Politics and government -- 1945-.